“MASNAVIYI MA’NAVIY”DA OLQISH ASOSIDA YUZAGA KELTIRILGAN ODDIY FOLKLORIZMLAR - Azimov, U.S. (SCIENCE and SOCIETY, 2021)
This article describes the use of proverbs, sayings, applause and curses in folklore texts, well studied in the literature. However, there is almost no research into how this process occurs in translated works. This article examines simple folklorisms found in the Uzbek translation "Masnaviyi ma’naviy / Cultural Treasures".